Light Absorption of GaN Nanowire Array Cathode with Alkali Metal Nanoparticle Modified on the Surface. (20th January 2021) - Liu, Lei; Lu, Feifei; Tian, Jian; Zhangyang, Xingyue
Abstract: Since the adsorption of alkali metals is necessary for the negative electron affinity (NEA) of the photocathode, light absorption models of GaN nanowire (NW) arrays with alkali metal (Li, Na, K, and Cs) nanoparticles (NPs) modified on the NW surface based on the finite difference time domain (FDTD) method are constructed. The absorption spectra of hemispherical, spherical alkali metal NPs adsorbed on the outer surface of the NW, and spherical alkali metal embedded on the inner surface and center of the NW are studied. When the ratio of NW diameter to period (D/P) is greater than 0.5, the adsorption of alkali metal NPs cannot improve the absorption of GaN NW arrays. Alkali metal decoration can cause the absorption gain of NW arrays and optical loss of NPs, so the diameter and spacing of alkali metal NPs need to be balanced. When Li NPs are embedded in NW, plasmons can enhance the generation of electron‐hole pairs, making GaN NWA obtain higher optical absorption and quantum efficiency. Therefore, the method of Li and Cs NPs embedded in GaN NW can provide a reference for the process NEA design, which will contribute to the development of the ultraviolet photocathode with high absorption characteristics. Abstract : The photo‐absorption and photoemission of the alkali metal (Li, Na, K, and Cs) nanoparticles (NPs) modified GaN nanowire (NW) arrays are investigated. Li NPs can obtain good average absorption (94.21%) when the particle diameter is 45 nm and the particle spacing is 50 nm. The method of Li NPs embedded into NWs makes a higher quantum efficiency.